2006
DOI: 10.4088/jcp.v67n0813
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Medications May Not Improve Outcome of Antipsychotic Monotherapy for Stabilized Patients With Nonacute Schizophrenia

Abstract: For most stabilized, chronic patients with schizophrenia, tapering adjunctive medications did not change outcome. This naturalistic study further defines the limits of efficacy of some concomitant classes of medications in patients with chronic schizophrenia who are already receiving adequate antipsychotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This complicated vicious circle might prolong the recovery from the other disorder, having probably created, in the case of schizophrenia, years ago, in Gruenberg's time, a type of chronic demoralization he had called "social breakdown syndrome" 12 . It has been observed that tapering of antidepressant medications in patients with stabilized non-acute schizophrenia may not improve the outcome of antipsychotic monotherapy; such patients were probably demoralized and psychotherapy might have been more useful 63 . In a study of patients with major depressive disorder, after controlling for depression severity at baseline, a greater degree of hopelessness was found to significantly increase the risk for non-response to fluoxetine as well as the risk of greater endpoint depression severity 64 .…”
Section: Discussionmentioning
confidence: 99%
“…This complicated vicious circle might prolong the recovery from the other disorder, having probably created, in the case of schizophrenia, years ago, in Gruenberg's time, a type of chronic demoralization he had called "social breakdown syndrome" 12 . It has been observed that tapering of antidepressant medications in patients with stabilized non-acute schizophrenia may not improve the outcome of antipsychotic monotherapy; such patients were probably demoralized and psychotherapy might have been more useful 63 . In a study of patients with major depressive disorder, after controlling for depression severity at baseline, a greater degree of hopelessness was found to significantly increase the risk for non-response to fluoxetine as well as the risk of greater endpoint depression severity 64 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Many patients in routine care settings continue to experience significant symptoms while following usual treatment regimens. 42 In other cases, antipsychotic polypharmacy may be the result of "getting stuck" in switching from 1 antipsychotic medi-*References 8, 9,11,12,17,21,26,40,41. Abbreviations: AOR, adjusted odds ratio; CI, confidence interval.…”
Section: Commentmentioning
confidence: 99%
“…Current antidepressant use was also associated with substantially decreased suicide deaths, whereas current benzodiazepine use was associated with marked increased risk for suicide. Because depressed, suicidal, and anxious patients are more likely than other patients to receive both antidepressants and benzodiazepines, the observed effect from these 2 classes of drugs may differ considerably in that antidepressant use may be beneficial and benzodiazepine use may be harmful in the treatment of patients with schizophrenia after their first hospitalization (but not necessarily among stabilized long-term patients 22 ). Moreover, catatonia and sleeping problems are 2 symptoms that might be more common among patients who receive benzodiazepines than among patients who receive antidepressants.…”
Section: Commentmentioning
confidence: 99%